Density Functional Theory (DFT) with Combined Investigation of the Selectivity of a Symmetrical Tetradentate N2O2-Coordination Schiff Base Ligand for Mn(II) Ion in the Presence of Mixing Mg(II), Mn(II), Ba(II), Ca(II) and Ni(II) Ions - Mahdeyeh SHEIKHSHOAIE; Vahid SAHEB; Tayebeh SHAMSPUR (Walailak Journal of Science and Technology, 2014)
Theoretical study and computational models are capable of reliably predicting ligand selectivity towards variety of metal ions, and can be valuable tools for the advancement of practical works. In this paper, a theoretical study based on the optimum angles and distance between a tetradentate Schiff base ligand and some metal ions is characterized. These investigations are carried out based on ab initio calculations to estimate the pair wise interaction energy between the 2 molecules. The calculations show that the mentioned ligand is a suitable ligand for the extraction of Mn(II) ions from a mixture of Ba(II), Mg(II), Mn(II), Ca(II) and Ni(II) ions.